The Outcome of Septic Abortion: A Tertiary Care Hospital Experience - Sreelakshmi, U. (Springer India, 2014)
OBJECTIVE: To study the incidence of septic abortion, reasons for that, sociodemographic profile, abortion providers, complications faced, and treatment given and its outcome. METHODS: All the women with septic abortion admitted at Government Maternity Hospital, Tirupathi, over a period of 2 years 4 months duration from July 2007 to October 2009 were studied prospectively. OBSERVATIONS AND RESULTS: Incidence of septic abortion in our study was 6.78 %. 72 % of cases were performed by qualified medical personnel. Fourteen patients had complications, among them peritonitis, pelvic abscess, renal failure, and septic shock were common. Twenty-six patients had Grade-I sepsis, Grade-II: 8, Grade-III: 4, and Grade-IV: 4. Laparotomy was done in six cases. There was no mortality in our study. CONCLUSION: The tragedy of septic-induced abortion is totally preventable. It only needs definitive commitment to women’s health by providing effective contraception, strengthening the family welfare services, and discouraging repeated terminations of pregnancy as contraceptive method.